Utilization of banana (Musa acuminata L, cv cavendishii) flour in the development of high-fiber soft taco shells - Pomarin, Mary Grace T. (2010)
The objective of this study was to utilize banana flour as a fiber source in the development of high-fiber soft taco shells and to assess its influence on the physical, chemical and organoleptic properties of the taco shells. In this study, Cavendish banana (Musa acuminata L, cv cavendishii) flour was used with all-purpose flour at the ratios of 30:70, 40:60 and 50:50 for soft taco shell processing. The three formulations were subjected to Preference Ranking and the data were analyzed using the Friedman test. The formulation containing the highest amount of banana flour (50:50) was used to prepare the final product since the three formulations were found to have no significant difference (P<0.05). The final product was evaluated according to overall quality, appearance, color, flavor and texture by a panel composed of 80 judges for the Consumer Acceptability Test using a 9-Point Hedonic Scale Rating. The data were analyzed using the Sign Test and it was found that its overall quality, appearance, color, flavor and texture were acceptable. Moreover, the final product was subjected to proximate analysis and some of its physical properties were assessed. It was found to contain 18.10% moisture, 1.77% crude ash, 7.30% crude fat, 6.97% crude protein, 64.70% carbohydrates and a crude fiber content of 1.16%. The crude fiber content is ten times greater than the crude fiber content of tortilla made from bleached wheat flour, which is only 0.1%. it has an average weight of 22.10 grams, an average diameter of 15.4 centimeters and an average thickness of 1.2mm. It is also found to be rollable up to 9 days when stored in a resealable low density polyethylene bag at room temperature and up to 30 days, when stored in the refrigerator.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2010
Keywords: Banana -- Cavendish; Flour; High-fiber soft taco shells; Taco shells; Banana flour; Organoleptic properties; Proxiamate analysis; Soft taco shells; Preference Ranking; Friedman test; Consumer Acceptability Test; 9-Point Hedonic Scale Rating